Geochemical signatures of parent materials and lake sediments in northern Minnesota - Mellicant, Emily (Kansas State University, 2017)
The importance of local parent material has been recognized as a fundamental control on the geochemistry of lake sediments, but there have been relatively few broad-scale surveys of catchment sources of terrigenous lake sediments. In this paper, I present a geochemical study of catchment parent materials and lake sediments from four lakes in Northern Minnesota. Similar climate and vegetation conditions are present at all four lakes, which vary mainly in catchment parent material and lake morphometry. Geochemical data including major, trace and rare earth elements (REEs) from catchment parent material samples was compared with lake sediment geochemical data using PCA, linear regression, geological indices and elemental ratios. In homogenous till-dominated catchments, patterns of elemental variation in the catchment till could be extended to predict elemental concentrations in the lake sediments. Simple ratios, which are commonly used to analyze lake sediment geochemical data, were not good predictors of lake sediment composition, however. Catchments with mixed bedrock and till were compositionally heterogeneous, and comparison with lake sediments was difficult. Lack of grain size control and biogenic silica measurements further confounded analysis. However, ΣREE/Y ratio was found to be diagnostic of the catchment parent materials and present within the lake sediments. This study makes a contribution to an improved understanding of lacustrine sedimentary archives by analyzing the spatial linkages among catchment, water and sedimentary geochemistry.
Keywords: Sedimentary geochemistry; Lake sediments; Lake catchments